2021
DOI: 10.3389/fnmol.2021.745219
|View full text |Cite
|
Sign up to set email alerts
|

Treatment With Nepicastat Decreases Contextual Traumatic Memories Persistence in Post-traumatic Stress Disorder

Abstract: Post-traumatic stress disorder (PTSD) is a common anxiety mental disorder and can be manifested after exposure to a real or perceived life-threatening event. Increased noradrenaline and adrenaline in plasma and urine have been documented in PTSD. Dopamine-β-hydroxylase (DBH) catalyzes the conversion of dopamine to noradrenaline and consequently, DBH inhibition reduces catecholamines. Our aim was to evaluate if nepicastat treatment decreases PTSD signs in an animal model. Wild-type (129x1/SvJ) female mice were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 85 publications
(144 reference statements)
0
19
0
Order By: Relevance
“…In clinical analysis, the correlation between sympathetic nerve activation and plasma or urine levels is controversial. In contrast, the correlation between them was verified in various rodent stress models [38][39][40]. As described before, sympathetic hyperactivity following a single oral dose of FLs may occur as a stress response [41].…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…In clinical analysis, the correlation between sympathetic nerve activation and plasma or urine levels is controversial. In contrast, the correlation between them was verified in various rodent stress models [38][39][40]. As described before, sympathetic hyperactivity following a single oral dose of FLs may occur as a stress response [41].…”
Section: Introductionmentioning
confidence: 76%
“…Determination of urinary CAs has been used to assess SNS activity induced by stressors in mammals [54]. Especially, the correlation between the activity of SNS and the level of plasma or urine CAs was verified in rodent stress models, such as social defeat [38], hypothermia [39], or PTSD models [40]. Oral administration of FLs likely activate SNS because they are considered stressors in rodent models.…”
Section: Discussionmentioning
confidence: 99%
“…On day 15, the EPMT was performed (Figure 1B), as formerly reported (Pellow et al, 1985;Fertan et al, 2019;Martinho et al, 2020;Gasparyan et al, 2021;Martinho et al, 2021). The experimental device was positioned 60 cm above the floor and comprised two open arms (40 × 10 cm) and two enclosed arms (40 × 10 cm with 20 cm high walls), displaying a total of four arms delimiting a central area of 5 cm 2 and arranged at right angles with equal arms facing each other.…”
Section: Elevated Plus-maze Testmentioning
confidence: 96%
“…PTSD research is highly dependent on several animal models that have originated from the use of various forms of trauma experiences ( Pynoos et al, 1996 ). The PTSD mice model chosen to be carried out in the present study is based on the concept that submission to electrical shocks leads the animals to develop PTSD’s pathophysiological processes and earliest complex symptoms and signs of the pathology, such as enhanced contextual traumatic memory and anxiety-like behavior ( Li et al, 2006 ; Zhang et al, 2012 ; Martinho et al, 2020 ; Martinho et al, 2021 ). Previously, we and others reported that the exposure to multiple foot shocks is efficient to replicate the traumatic episode in this model ( Li et al, 2006 ; Zhang et al, 2012 ; Verma et al, 2016 ; Martinho et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation